DEVELOPING LEARNING MEDIA OF VOLLEYBALL FOR VOCATIONAL HIGH SCHOOL STUDENTS - Haryanto, Andung Dwi (Journal Physical Education, Health and Recreation, 2020)
The study aims to produce volleyball learning media for vocational students referring to the 2013 curriculum. The research type is R & D, with steps: (1) preliminary study, (2) initial draft design, (3) validation of initial draft, (4) ) small-scale trials, (5) large-scale trials, (6) final product, and (7) effectiveness test. Small-scale trial at SMK Negeri 1 Pejawaran. Large-scale trials at SMK Negeri 1 Wanayasa and SMK Negeri 1 Punggelan. Effectiveness Test at SMK N 2 Bawang. The instruments are: (1) interview guide, (2) questionnaire, (3) and multiple choice test. Analysis of quantitative and qualitative descriptive data, t test on effectiveness test. The result of the research is volleyball learning media for vocational students which refers to the curriculum 2013. Packed in one piece Compact Disc containing elements of text, images, video and sound. The volleyball learning media for vocational students referring to the 2013 curriculum can effectively improve students' understanding.